Implementation of Building Use Rights in State Land Management by Developers - Supriyanto Supriyanto; Azis Budianto; Faisal Santiago (Riviera Publishing, 2024)
Management of state land through Building Rights (HGB) is an important issue in infrastructure development and economic investment in Indonesia. The problems faced include complex bureaucracy, conflicts of interest, and lack of supervision in the implementation of HGB. This study aims to analyze the implementation of HGB in the management of state land by developers and its impact on infrastructure development and economic growth. The research methods include literature studies and policy analysis covering regulations and best practices in the field. The results of the study indicate that effective implementation of HGB can encourage investment, create jobs, and improve access to public facilities. However, challenges such as regulatory complexity and potential conflicts of interest need to be addressed through collaboration between the government and developers. The implications of this study are the importance of implementing transparent governance, clear regulations, and legal protection to ensure sustainable and inclusive management of state land.